The Framework of Collective Action and its Cultural Implications for the Construction of Citizenship - Ricardo Delgado Salazar (Universitas Humanística, 2007)
The present considerations seek to emphasize the approaches of the framework of collective action theory and identify those components that allow us to understand the “agentization” of social movements as renewed expressions of citizenship. The framework of collective action theory allows us to gain a better understanding about the sense and the meaning that the members of an organization or social movement ascribe to the experience of participating and mobilizing citizens.